Analisis Obyek Uji Pada Tomografi Komputer Dengan Menggunakan Resolusi Rendah, Menengah Dan Tinggi - Nur Kholis (Teknika, 2010)
Abstract Computer Tomography  is a medical equipment that is used to identify the internal organs. In the process used when counter to scanning approximately 5000 ms in every good resolution of low-resolution, high in the middle and kolimator scanning using 5 mm, based on testing kolimator 1 mm, 3 mm produces a less clear image, it is because the energy received by a radioactive detector will be exhausted. Image szxe at low resolution 31 pixels x 31 pixels, high resolution of 63 pixels x 63 pixels and high resolution 127 pixels x 127 pixels. Results from high-resolution reconstruction has a more obvious when compared with low and medium resolution, due to more number of pixels and the time required in the longer counters. The results of scanning a result of projected sinogram and reconstructed image produced. Results of numerical and visual and the result is the same as the original test objects, at high resolution has the average e-max 0,196%.